Acquire or Integrate the Provider? The Dilemma of a Company: a Model of Game Theory Applied (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional De Tecnología, Ciencia Y Sociedad, 2019)
Sometimes, the size of a company exceeds the level of sales and generates losses; to reduce them, it is proposed that the company incorporates its supplier. Such incorporation can be done in two ways: i) acquire it completely, or ii) associate it. An imperfect information model is built for the company, and the types of suppliers that exist are determined. Based on a signal from the provider, a threshold is derived from which it is beneficial for the company to incorporate the supplier. In addition, 50% could be granted to the provider if it is of healthy finances.